Effectiveness Of Lavender Aromatherapy In Reducing Active First-Stage Labor Pain At PMB Komariyah - Rita Setyorini; Tut Rayani Aksohini Wijayanti (Journal of Innovative and Creativity, 2025)
Labor pain in the active phase of the first stage is a major complaint among laboring women. This quasi-experimental study aimed to evaluate the effectiveness of lavender aromatherapy inhalation in reducing labor pain during the active phase of the first stage. A total of 32 women were assigned to intervention (n=16) and control (n=16) groups. The intervention group received 5% lavender essential oil inhalation every 2 hours for 10 minutes, while the control group received standard midwifery care. Pain intensity measured using the Numeric Rating Scale significantly decreased in the intervention group (from 7.81 ± 1.17 to 4.13 ± 1.02) compared with the control group (from 7.69 ± 1.08 to 6.88 ± 1.15) (p < 0.001). Lavender aromatherapy is effective as a complementary method to reduce labor pain in primary midwifery care. Lavender aromatherapy is recommended as a complementary non-pharmacological method for labor pain management in primary obstetric care.